Pathogenicity of porcine sapelovirus infection in mice - KUMARI, SWATI; RAY, P K; SINGH, RAHUL; SAIKUMAR, G (The Indian Journal of Animal Sciences, 2019)
Porcine Sapelovirus (PSV) is a RNA virus belonging to a new genus Sapelovirus of family Picornaviridae. PSV has been isolated from India in 2016. In the present study, mice experiment was conducted to detect the ability of PSV to infect mice and its ability to induce pathological lesions. The intestinal and extra intestinal spread of the PSV virus in three week-old Swiss albino mice inoculated with PSV virus quantified by probe based real time PCR are described. Herein, three groups were made with 10 mice per group (both sex). The first group was infected through oral route (8Ã—106, TCID50, 240 Î¼l/mice) while the second through intra-peritoneal route (8Ã—106, TCID50, 240 Î¼l/mice) and the third group was inoculated with PBS of neutral pH orally and intra-peritoneal route. Seven mice (each from oral and intraperitoneal route and three from control group were sacrificed at 5th, 7th, 9th, 12th, 15th, 17th, 21st day post infection (DPI). Indian strain was able to replicate in mice organs up to 15 DPI in oral route and 9 DPI in intraperitoneal route. By real-time reverse transcription (RT) PCR, PSV was detected in most of the organs but with highest viral load in the small intestine and large intestine than extra-intestinal organs in the orally infected mice. In addition, this Indian strain is enteropathogenic but could spread to the bloodstream from the gut and disseminate to extra-intestinal organs. These results will contribute to our understanding of PSV pathogenesis.